2008
DOI: 10.1063/1.3043879
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic electroforming behavior in Pt/TiO2/Pt resistive switching cells depending on atmosphere

Abstract: Electroforming effects on the composition, structure, and electrical resistance of Pt/ TiO 2 / Pt switching cells are investigated. The correlation between the electroforming procedure and the resulting bipolar switching behavior is discussed. The dependence of electroforming behavior on atmosphere is also identified, from which we define symmetric or asymmetric electroforming. The symmetry of electroforming is a key factor determining the resulting bipolar switching characteristics. From the experimental resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
234
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(247 citation statements)
references
References 13 publications
11
234
0
2
Order By: Relevance
“…This is a strong indication that the electroforming pro- cess is a local phenomenon, e.g., due to the formation of a conducting filament. These findings are consistent with results found in TiO 2 devices by Jeong et al 9 and Yang et al 20 …”
Section: A Filamentary Versus Homogeneous Effectsupporting
confidence: 93%
See 3 more Smart Citations
“…This is a strong indication that the electroforming pro- cess is a local phenomenon, e.g., due to the formation of a conducting filament. These findings are consistent with results found in TiO 2 devices by Jeong et al 9 and Yang et al 20 …”
Section: A Filamentary Versus Homogeneous Effectsupporting
confidence: 93%
“…16 Szot et al 17 demonstrated that, using SrTiO 3 single crystals, the electroforming process removes oxygen ions from the crystal lattice which becomes evident by the appearance of gas bubbles under the anode. The evolution of oxygen gas bubbles was also observed in thin film Pt/ TiO 2 / Pt samples by Jeong et al 9 and Yang et al 10 Conductive atomic force microscopy ͑LC-AFM͒ measurements performed on SrTiO 3 single crystals 17 and epitaxial thin films 18,19 indicated a laterally confined and filamentary current transport within the material. The conducting filaments were attributed to extended defects such as edge dislocations.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…The migration of charged oxygen vacancies is the mostly cited mechanism responsible for the RS behavior observed in a wide range of sandwich-type oxide-based devices [34,[74][75][76][77][78]. However, as proposed by Liu and co-workers, the trapping or detrapping of electrons in the defect-derived quasiconduction band in 150-nm-thick LAO films can lead to the overlap of wave functions and the reversible insulator-metal transitions [68].…”
Section: Discussionmentioning
confidence: 99%